2020
DOI: 10.3390/biom10121698
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Lipids in Health and Disease

Abstract: Although the primordial concept of lipids is associated with the role they play as key components of the cell membrane, growing research in the field of bioactive lipids and lipidomic technologies proves the prominent role of these molecules in other biological functions [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Over the past two decades, it has been shown that bioactive lipids may act as immunomodulators, reducing inflammation and helping to maintain tissue homeostasis, and some are constituents of cell membranes and energy substrates [59]. Via these effects, bioactive lipids help to prevent various diseases, such as cancer, heart disease, obesity, and neurodegenerative disorders [60].…”
Section: Roles Of Bioactive Compoundsmentioning
confidence: 99%
“…Over the past two decades, it has been shown that bioactive lipids may act as immunomodulators, reducing inflammation and helping to maintain tissue homeostasis, and some are constituents of cell membranes and energy substrates [59]. Via these effects, bioactive lipids help to prevent various diseases, such as cancer, heart disease, obesity, and neurodegenerative disorders [60].…”
Section: Roles Of Bioactive Compoundsmentioning
confidence: 99%
“…They also undergo β‐oxidation in mitochondria with the help of peroxisomes. In Lands cycle, more than 90% of DHA and AA released from the phospholipid membrane are rapidly re‐esterified to phospholipids, whereas a proportion of these unesterified fatty acids can be used as substrates for the synthesis of pro‐inflammatory and pro‐resolving mediators after enzymatic conversion by cyclooxygenase, lipoxygenase and cytochrome P450, which is demonstrated in Figure 3 (the omitted part can be visible from Bari et al, 2020). Reprinted by permission from Bazinet and Layé (2014)…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Bioactive lipids have been shown to participate in regulating complex pathways. They may be involved in homeostasis, initiation and resolution of inflammation, as well as disease pathologies, including cancer, heart disease, obesity, viral infection (such as coronavirus disease 2019) and neurodegenerative disorders (Bari et al, 2020; Theken & FitzGerald, 2021). Their broad physiological functions suggested that the administration of bioactive lipids might potentially prevent and treat certain diseases, such as PD.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous functions executed by these lipids are matched by the diversity of the groups that are within the bioactive lipids. These species include the following major classes: eicosanoids, phospholipids, sphingolipids, endocannabinoids, and the newly discovered specialized pro-resolving lipid mediators (SPMs) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%